Physical and Mental Burden of Ocular Surface Squamous Neoplasia on Health-Related Quality of Life - Widyanti Soewoto; Senyum Indrakila; Joko Purnomo; Erma Malindha; Yusuf Vindra Asmara (Majalah Kedokteran Bandung, 2026)
Patients diagnosed with ocular surface squamous neoplasia (OSSN) often experience a significant decline in health-related quality of life (HRQoL) due to its potential for visual impairment. This study aimed to investigate the association between OSSN and HRQoL by considering various determinants. A case-control study was conducted at Dr. Moewardi General Hospital, Indonesia, from May to December 2024. A total of 324 respondents, 162 in each group, were sampled consecutively and enrolled in this study. The OSSN patients group and the control group consisted of 97 males (59.9%) and 65 females (40.1%). The HRQoL was evaluated using the RAND Short Form Health Survey (SF-36), focusing on physical health composite (PHC) and mental health composite (MHC) scores. All procedures adhered to the established ethical guidelines. Data were analyzed using multivariate regressions in IBM SPSS version 26. Result showed that OSSN significantly impacted HRQoL. Low PHC scores were prevalent in 48.1% of OSSN patients, compared to 50.6% in controls, with an odd ratio [OR] of 2.68 and p<0.05. The MHC scores showed a similar trend, with 49.0% of OSSN patients reporting low scores (OR: 2.56, p<0.05). Furthermore, the stratified analysis showed that younger males were particularly affected, with lower HRQoL scores across all domains. Overall, OSSN imposes physical and mental burdens, significantly reducing HRQoL. Thus, a holistic treatment method that integrates both the physical and psychological health supports for OSSN patients is needed. Awareness raising and early detection initiatives may further mitigate the adverse effects of OSSN on life quality.